The Greek version of the 9-item European heart failure self-care behaviour scale: A multidimensional or a uni-dimensional scale? - Lambrinou, Ekaterini; Kalogirou, Fotini; Lamnisos, Demetris; Papathanassoglou, Elizabeth; Protopapas, Andreas; Sourtzi, Panayota; Barberis, Vassilis I. I.; Lemonidou, Chrysoula; Antoniades, Loizos C.; Middleton, Nicos (My University, 2014)
Objectives: To evaluate the dimensionality of the Greek version of the European Heart Failure Self-care Behaviour Scale (Gr9-EHFScBS) in a Greek e Cypriot population.Background: EHFScBS is a valid and reliable scale which is widely used for assessing heart failure (HF)patients’ self-care behaviors. Methods: EHFScBS was translated into Greek and was administered to 128 Greek-Cypriot HF patients. The internal consistency, construct validity and discriminant validity of the scale were assessed.Results:Confirmatory factor analysis failed to capture the proposed theoretical structure. Further exploratory factor analysis provided a three-factor solution accounting for 53.35% of the variance, though the scale is better used as a whole. Cronbach’s alpha was moderate 0.66, but deletion of any item decreased the alpha coefficient. Discriminant validity was supported by the poor correlation between EHFScBS and Minnesota Living with Heart Failure Questionnaire scores.Conclusion: Even though results do not conform to themultidimensionality of the scale, assessment of the tool provided acceptable validity and reliability measures to support its usage among Greek speaking populations.
Keywords: European heart failure self-care behaviour scale; Heart failure; Self-care; Psychometric properties; Questionnaire